MISI KRISTEN DI ERA POSTMODERN: TANTANGAN RELATIVISME DAN RESPON TEOLOGIS TERHADAP PEMBERITAAN INJIL - Armin Paipi; Indhasari, Marlina Kumuku, Jeskawati Sita'pa, Yusnita Ratte (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research is titled "Christian Mission in the Postmodern Era: The Challenge of Relativism and Theological Responses to the Proclamation of the Gospel" aims to explore the challenges faced by the church in the context of mission amid social and cultural changes characterized by postmodern thinking. The postmodern era emphasizes relativism, where truth is considered subjective and bound to individual experience, leading to questioning and rejection of the absolute truth claims found in Christian teachings. Through a literature review, this study analyzes the dynamics of relativism and its implications for how the church proclaims the Gospel. Additionally, this research examines the appropriate theological responses to address these challenges, including the importance of contextualizing the proclamation of the Gospel, relational approaches, and interfaith dialogue. This study emphasizes that the church must develop mission strategies that are relevant and responsive to societal needs without compromising biblical truth. The findings of this research are expected to provide insights and recommendations that will be beneficial for the church and mission organizations in formulating effective approaches to reach postmodern society with an authentic and transformational message of the Gospel. Thus, this research contributes to the development of Christian missiology that is relevant in the context of a constantly changing era